Prevalence and anatomical distribution of incidental and actionable findings on CBCT scans for implant planning - Shrey Pandya; Swarna Yerebairapura Math; Justin Kim; Adnan Shah; Saranjeev Lalh; Camila Pacheco-Pereira (PLoS ONE, 2026)
Objectives To determine the prevalence and anatomical distribution of incidental (IF) and actionable findings (AF) on cone-beam computed tomography (CBCT) scans obtained for dental implant planning, and to evaluate their associations with patient demographics and imaging parameters. Materials and Methods This retrospective observational study included all consecutive CBCT scans obtained for implant planning (n = 368). A structured, zone-based evaluation protocol was applied, systematically assessing four anatomical regions: (1) cranium and paranasal sinuses, (2) zygomaticomaxillary/orbital complex including the temporomandibular joint, (3) maxillomandibular region, and (4) structures inferior to the mandible. IF were defined as findings unrelated to the implant planning site, and AF were classified based on the oral and maxillofacial radiologist recommendations for further evaluation, referral, or management rather than confirmed clinical outcomes. Associations between IF, AF, CBCT field of view (FOV), age, and sex were analyzed using univariate and multivariable methods. Results IF were observed in 257 patients (69.8%) and AF in 199 (54.1%). IF prevalence increased from 50% in patients ≤40 years to 78.8% in those >70 years, and was higher in males than females (76.2% vs. 64.5%; p = 0.01). In univariate analyses, AF were not significantly associated with sex (p = .97) or age (p = .25). However, patients >70 years had higher odds of AF in multivariable analysis, although the overall model was not statistically significant. Zone 2 findings were more common in females than males (21.5% vs. 7.1%; p < 0.001). IF were most common in medium FOV scans (72.2%), whereas AF did not vary by FOV ( p = .94). The most prevalent findings involved the maxillary sinus (35.1%), cervical spine (27.4%), tonsils (15.8%), TMJ (11.7%), and vasculature (8.4%). Conclusions IF and findings classified as AF based on OMR recommendations were highly prevalent in CBCT scans obtained for implant planning. Approximately half of the scans presented AF (54%). These findings were distributed across multiple anatomical zones and were associated with age and sex, while AF showed no association with FOV.